Non-invasive evaluation of muscle disease in the canine model of Duchenne muscular dystrophy by electrical impedance myography. - Chady H Hakim; Alex Mijailovic; Thais B Lessa; Joan R Coates; Carmen Shin; Seward B Rutkove; Dongsheng Duan (PLoS ONE, 2017)
Dystrophin-deficient dogs are by far the best available large animal models for Duchenne muscular dystrophy (DMD), the most common lethal childhood muscle degenerative disease. The use of the canine DMD model in basic disease mechanism research and translational studies will be greatly enhanced with the development of reliable outcome measures. Electrical impedance myography (EIM) is a non-invasive painless procedure that provides quantitative data relating to muscle composition and histology. EIM has been extensively used in neuromuscular disease research in both human patients and rodent models. Recent studies suggest that EIM may represent a highly reliable and convenient outcome measure in DMD patients and the mdx mouse model of DMD. To determine whether EIM can be used as a biomarker of disease severity in the canine model, we performed the assay in fourteen young (~6.6-m-old; 6 normal and 8 affected) and ten mature (~16.9-m-old; 4 normal and 6 affected) dogs of mixed background breeds. EIM was well tolerated with good inter-rater reliability. Affected dogs showed higher resistance, lower reactance and phase. The difference became more straightforward in mature dogs. Importantly, we observed a statistically significant correlation between the EIM data and muscle fibrosis. Our results suggest that EIM is a valuable objective measurement in the canine DMD model.